Moral Communities in Anti-Doping Policy: A Response to Bowers and Paternoster. Issue 1 (2nd January 2019) - Macedo, Emmanuel; Englar-Carlson, Matt; Lehrbach, Tim; Gleaves, John
Abstract: This article argues that Bowers and Paternoster's emphasis on a moral community marks an important step towards a more ethical and effective approach to anti-doping. However, it also argues that the authors' proposed strategies undermine their stated goal of effectively engaging athletes as partners in anti-doping efforts and raise ethical concerns. Their proposed emphasis on exploiting shaming as a punishment and their general view of athletes as adversaries fosters mistrust between athletes and those who enforce the anti-doping rules. Instead, this article describes a model for empowering athletes as stakeholders in anti-doping policy as a means to provide anti-doping rules with increased moral legitimacy among athletes.